La política agraria en el Yucatán colonial: las composiciones de tierras en 1679 y 1710 - Carrera Quezada, Sergio Eduardo (El Colegio de México, A.C., 2015)
This article addresses an overlooked issue in Yucatecan historiography: the concession of idle land and land use policy during the colonial period. It analyzes the motives for which the Spanish almost never took advantage of the land titles granted freely by the crown when establishing their ranches, but instead preferred to purchase land, wells and cenotes from local caciques and noble Maya families. It also shows the particular characteristics of regional land use policy, such as the reasons for its late implementation, the negotiations between ranchers and judges and the exclusive benefits for Spaniards. The article concludes by explaining the various methods Yucatecan Mayas used to defend their right to the land they had possessed since time immemorial.